Role of failed renal allograft embolization in the treatment of graft intolerance syndrome - Hindi, Hussam; Harb, Ali (Journal of Clinical Imaging Science)
Nearly, 20% of renal allografts fail after 5 years resulting in a return to hemodialysis. These patients subsequently undergo withdrawal of immunosuppressant therapy, and the failed allograft is left in situ. However, many patients (40%) develop graft intolerance syndrome, characterized by fever, pain, and hematuria. Conventionally, this is managed with low-dose maintenance immunosuppressant therapy, however, that is not without notable adverse risk. In refractory patients, transplant nephrectomy is the treatment of choice; however, this caries significant morbidity and mortality. Interventional radiology plays a substantial role of treating graft intolerance syndrome while delivering improved patient outcomes.